Sales expense strategies for competitive pricing of industrial building system (IBS) components - Aziz, N. D.; Ishak, M. F.; Omardin, M. A.; Zulkiple, A.; Mohamed, Y. (IOP Publishing Ltd., 2021)
The pandemic situation demand the construction player need to consider to re-evaluate architecture design. The issue of shortage of skilled workers due pandemic and method of traditional construction involving longer period and close contact among labours questioned in many countries. Therefore, industrial building system (IBS) or modular construction involves using pre-made modules created in a factory and brought to construction sites for assembly is one of method is recommended to overcome the issue during pandemic period. Nevertheless, The Malaysian IBS manufacturing player faced the difficult to achieve economies of scale due to higher capital cost and this problem caused by high operational cost in manufacturing. In marketing a product, sales expense is crucial to ensuring that a product can be sold in large quantities. In this study, sales expense variables among the established the cost control parameter required by IBS manufacturer that seeking for lower and stable market prices will be discuss in detail. To achieve the study objective. Thus, in this study, six (6) case studies from reliable data in the theme competitive pricing will be selected in this quantitative study. In a nutshell, this study explores China's perception in term of competitive pricing of IBS components as per recommendation by many scholars. Using semi structure measurement instrument, the recorded data gained in this study later, transcribed using Atlas. Ti software. Also, the study is expected might help the Malaysian IBS manufacturer to realise the sales-related expenses strategies that need to be invested that might boost IBS demand in their enterprises.